Optimize the conversion of lignocellulosic agricultural by-products to bio-ethanol using different enzyme cocktails and recombinant yeast strains - Mubazangi M (2012)
Please help us populate SUNScholar with the post print version of this article. It can be e-mailed to: scholar@sun.ac.za